Shar`ah perspectives of Investment Risk Management: a case study of Islami Bank Bangladesh Limited - Osmani, Noor Mohammad; Amin, Faroque (2010)
Within a period of about twenty-eight years since its establishment in 1983, the first interest-free Shari`ah-based bank of South and Southeast Asian region; Islami Bank Bangladesh Limited (IBBL), has recently become top ranked bank of private sector in Bangladesh. Having a wide range of investment schemes, IBBL has been dealing with the issue of risk management successfully. This study will attempt to analyze and represent the nature and development of risk management policy of IBBL with the focus on its Shari`ah-compliance issues. It will investigate the impact of Shari`ah-compliance of risk management instruments with its success in banking, and in the investment in particular. In doing so, a major focus of discussion would be given for scrutinizing the status of that policy in relevance with the issues of Islamic jurisprudence. Accordingly, an attempt to represent a brief comparison of that Shari`ah-compliant policy with conventional and prominent risk management principles will take place. The qualitative nature of this research would require study of references and primary resource materials as well as gathering data from different dynamic sources. The research reached at certain conclusions that, the risk management policy played a key role in the success of IBBL. That policy is also Shari`ah-compliant, as asserted in the literatures of IBBL and other sources. Most importantly, it will initiate an opportunity to share the analysis of relevant principles and policies of IBBL along with a discussion of their Shari`ah perspectives.